Does inhabitant’s fertility intention respond to housing status in the urban built environment: evidence from China - Xuefang Zhuang; Qingyin Li; Tian Su; Siying Zhang; Rong Wu; Tianxiang Zheng (Frontiers in Public Health)
BackgroundThe total fertility rate in China has been dropping in recent years, and this continuing trend has led to a series of problems. China has experienced periods of urbanization and housing reforms, leading to a significant boom in the real estate market. Housing status appears to be an essential factor influencing the fertility-related decisions of residents in China.MethodsWe use cross-sectional data from a nationally representative large-scale tracking survey targeting the labor force in China. The research sample for this study comprised data from Chinese adults between the ages of 20 and 45. We highlight the importance of housing mortgages on fertility intention based on the Poisson regression model.ResultsData was collected from a total of 7,512 inhabitants. The results show the following: 1) Housing status is closely related to fertility intention, while housing mortgage and water contamination are negatively affected. 2) The urban built environment, social environment, and individual characteristics affecting fertility intention mainly occur in urbanization rate, green coverage rate in urban built-up areas (GCR), life satisfaction, mental health, age, gender, marital status, political status, and education status. Urbanization rate, GCR, life satisfaction, and mental health positively influence resident’s fertility intention, whereas women and single show lower fertility intention. 3) In particular, there are significant regional differences in the mechanism of fertility intention. Such intention in the eastern and central regions is primarily related to housing mortgages, urban built environment, the degree of contamination in the habitat, and socioeconomic factors, while the intention in the northeastern region is related to soil contamination. Fertility intention in the western and northeastern region are strongly related to mental health.